Malaria Related Neurocognitive Deficits and Behavioral Alterations - Rosa-Gonçalves, Pamela; Ribeiro-Gomes, Flávia Lima; Daniel-Ribeiro, Cláudio Tadeu (Frontiers in Cellular and Infection Microbiology, 2022)
Typical of tropical and subtropical regions, malaria is caused by protozoa of the genus Plasmodium and is, still today, despite all efforts and advances in controlling the disease, a major issue of public health. Its clinical course can present either as the classic episodes of fever, sweating, chills and headache or as nonspecific symptoms of acute febrile syndromes and may evolve to severe forms. Survivors of cerebral malaria, the most severe and lethal complication of the disease, might develop neurological, cognitive and behavioral sequelae. This overview discusses the neurocognitive deficits and behavioral alterations resulting from human naturally acquired infections and murine experimental models of malaria. We highlighted recent reports of cognitive and behavioral sequelae of non-severe malaria, the most prevalent clinical form of the disease worldwide. These sequelae have gained more attention in recent years and therapies for them are required and demand advances in the understanding of neuropathogenesis. Recent studies using experimental murine models point to immunomodulation as a potential approach to prevent or revert neurocognitive sequelae of malaria.